Detaching reasons from aims: Fair play and well-being in soccer as a function of pursuing performance-approach goals for autonomous or controlling reasons - Vansteenkiste, M.; Mouratidis, A.; Lens, W. (Journal of Sport and Exercise PsychologyJournal of Sport and Exercise Psychology, 2010)
In two cross-sectional studies we investigated whether soccer players' well-being (Study 1) and moral functioning (Studies 1 and 2) is related to performance-approach goals and to the autonomous and controlling reasons underlying their pursuit. In support of our hypotheses, we found in Study 1 that autonomous reasons were positively associated with vitality and positive affect, whereas controlling reasons were positively related to negative affect and mostly unrelated to indicators of morality. To investigate the lack of systematic association with moral outcomes, we explored in Study 2 whether performance-approach goals or their underlying reasons would yield an indirect relation to moral outcomes through their association with players' objectifying attitude-their tendency to depersonalize their opponents. Structural equation modeling showed that controlling reasons for performance-approach goals were positively associated with an objectifying attitude, which in turn was positively associated to unfair functioning. Results are discussed within the achievement goal perspective (Elliot, 2005) and self-determination theory (Deci & Ryan, 2000). © 2010 Human Kinetics, Inc.
Keywords: Achievement goal theory; Autonomous and controlled regulation; Performance-approach goals; Self-determination theory; Soccer; Sportspersonship; Well-being